Efficacy of Dinoprost in induction / synchronisation of behavioural estrus in subestrus Murrah Buffaloes - SHUKLA, M K; DABAS, Y P S (The Indian Journal of Animal Reproduction, 2007)
Twenty lactating Murrah buffaloes reared in semi intensive system under optimal conditions of feeding and management were selected for the study. The first group (n=IO) received two injections of 5 ml (25 mg) Lutalyse (Dinoprost thromethamin) intramuscularly 11 days apart whereas, the second group (n=IO) received the same volume of Normal Saline Solution at 11 days interval. The animals were thoroughly observed for signs of behavioural heat following treatment and bred with elite Murrah bulls at 72 and 96 hours after second injection of Lutalyse. Out of the 10 animals of the group first, 4 responded to the first injection whereas 8 animals showed behavioural estrus at 36 to 72 hours after the second injection. Two buffaloes failed to show behavioural estrus even after two treatments of Lutalyse but confirmed for estrus per-rectally at 72 hours following the second injection. Only two animals (20 %) of the control group exhibited behavioural heat during the period of study. The onset of behavioural estrus in control (20 %) and Prostaglandin treated group (80 %) differed significantly (P<0.05).